PENGARUH METODE DEMONSTRASI TERHADAP HASIL BELAJAR PEMELIHARAAN SASIS DAN PEMINDAH TENAGA KENDARAAN RINGAN KELAS XI TKR SMK NEGERI 1 MOTOLING - frando runtunuwu; Hendro Sumual; Jenly Manongko (GEARBOX: Jurnal Pendidikan Teknik Mesin, 2021)
THE EFFECT OF DEMONSTRATION METHODS ON LEARNING RESULTS OF SASIS AND MANAGEMENT MAINTENANCE LIGHTWEIGHT VEHICLE CLASS XI TKR SMK NEGERI 1 MOTOLING By: FRANDO RUNTUNUWU NIM 14 212 036 Supervisor : Dr. H. M. Sumual, ST, M.Eng Ir. D. J. I. Manongko, M.Eng ABSTRACT This study aims to determine and analyze the effect of demonstration methods on learning outcomes applying manual transmission maintenance at SMK Negeri 1 Motoling. This research method uses a quantitative approach, using the experimental method. Namely a method that is directed at solving problems by describing or describing what the research results are. The results showed that the effect of the demonstration method can significantly improve student learning outcomes in the Subject of Light Vehicle Chassis Maintenance at SMK Negeri 1 Motoling. Effect of learning Demonstration method through statistical tests using t-test, it turns out that the value of t is greater than t table or t = 3.071> t table = 1.684 at α = 0.05 dk = n - 2.Thus this study accepts the alternative hypothesis (Ha) and rejecting the normal hypothesis (H0) means that there is an effect of Demonstration Method Learning on student learning outcomes in the subject of Light Vehicle Chassis Maintenance at SMK Negeri 1 Motoling. . Keywords: Demonstration Method, Learning Outcomes and SPT TKR.